Response of Biochemical Characteristics and Grain Yield Of Canola (Brassica Napus L.) To Biofertilizers (Bangladesh Journal of Botany, 2021)
Effects of Mycorrhiza and Azotobacter biofertilizers on the biochemical properties and grain yield of rapeseed cultivars were investigated in a randomized complete block design with four replications in two years 2016 and 2017 in Khorramabad, Lorestan province, Iran. Biofertilizer factors included application of Mycorrhiza, Azotobacter, Mycorrhiza and Azotobacter combination and non-application of biofertilizer (control) and cultivar factors included Gabriella, Neptune, Expower and Okapi. According to interaction effect of biofertilizers × cultivar, results showed that the highest seed and oil yields were obtained with the application of Mycorrhiza and Azotobacter combination in case of Gabriella (4918.6 and 1165.2 kg/ha, respectively) and the least was found with non-application of biofertilizers in case of Expower (3350.4 and 731.3 kg/ha, respectively). Biochemical parameters like shoot proline, protein, peroxidase, catalase, Chlorophyll a and b content of canola were also significantly affected by biofertilizer, cultivar and due to interaction of biofertilizer and cultivar. Therefore, application of Mycorrhiza and Azotobacter combination in case of Gabriella is recommended for Khorramabad and similar regions.Bangladesh J. Bot. 50(3): 585-593, 2021 (September)